‘First, Do No Harm’: The Role of Negative Emotions and Moral Disengagement in Understanding the Relationship Between Workplace Aggression and Misbehavior - Fida, Roberta; Tramontano, Carlo; Paciello, Marinella; Guglielmetti, Chiara; Gilardi, Silvia; Probst, Tahira M.; Barbaranelli, Claudio (Frontiers in Psychology, 2018)
Workplace aggression is a critical phenomenon particularly in the healthcare sector, where nurses are especially at risk of bullying and third-party aggression. While workplace aggression has been frequently examined in relation to health problems, less is known about the possible negative impact such aggression may have on the (un)ethical behavior of victims. Our research aims to fill this gap. Drawing on literature on counterproductive work behavior and the social-cognitive literature on aggression we investigated in two independent studies (NStudy1 =439; NStudy2 =416), the role of negative emotions - in particular anger, fear, and sadness, - and of moral disengagement in the paths between workplace aggression, counterproductive work behavior and health symptoms. The focus on these relationships is rooted in two reasons. First, misbehavior at work is a pervasive phenomenon worldwide and second, little research has been conducted in the healthcare sector on this type of behavior despite the potential importance of the issue in this context. We empirically tested our hypotheses considering a specific form of workplace aggression in each study: workplace bullying or third-party aggression. Results from the two empirical studies confirm the hypotheses that being target of workplace aggression (bullying or third-party aggression) is not only associated with health symptoms but also with misbehavior. In addition, the results of structural equation modelling attest the importance of examining specific discrete negative emotions and moral disengagement for better understanding misbehavior at work. In particular, this research shows for the first time that anger, fear, and sadness, generally aggregated into a single dimension, are indeed differently associated with moral disengagement, misbehavior and health symptoms. Specifically, in line with the literature on discrete emotions, while sadness is only associated with health symptoms, anger and fear are related to both health and misbehavior.